From Knowledge to Practice: Enhancing Teacher Competence through a Life Skills-Based Module in the Merdeka Belajar Curriculum - Padang, Nita Sampe; K, Nurdin; Salmilah, Salmilah (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palopo), 2025)
The implementation of the Merdeka Belajar Curriculum in Indonesia requires teachers not only to understand policy principles but also to apply them effectively in classroom practice. However, many teachers face challenges in enacting differentiated instruction, indicating a gap between conceptual understanding and practical readiness. This study aimed to develop, validate, and evaluate a life skills-based module to enhance teacher competence in implementing the Merdeka Belajar Curriculum. The study followed the ADDIE model, Analysis, Design, Development, Implementation, and Evaluation, employing a research and development design with a mixed-method approach. Data were collected at SMPIT Ibnu Sina Palopo from 12 participating teachers through questionnaires, expert validation sheets, teacher response instruments, pre-test and post-tests, interviews, and documentation. Quantitative data were analyzed descriptively and through gain scores, while qualitative data were examined thematically. The results indicated that teachers possessed adequate conceptual understanding of the curriculum but limited readiness to apply differentiated learning strategies. The developed module was rated highly valid by content, language, and design experts and assessed as practical by teachers during pilot implementation. Effectiveness testing showed significant improvement in teacher competence after using the module, supported by qualitative evidence of increased confidence and adaptability. In conclusion, the life skills-based module successfully bridged the gap between theoretical knowledge and classroom practice, confirming the importance of embedding personal, social, academic, and vocational competencies into teacher professional development. The study contributes to curriculum innovation and teacher training by offering a structured, practice-oriented resource that supports the successful enactment of the Merdeka Belajar Curriculum in Indonesian secondary schools.